Karbala in the Taʿziyeh Episode, Shi'i Devotional Drama in Iran - Deacon, Lucy, (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
"I am not Shemr, this is not a dagger, nor is this Karbala," recites the arch-antagonist as a taʿziyeh performance begins. Verisimilitude is not the endeavour; this is a devotional offering that stirs lament for the Shi'i martyrs by representing events crucial to sacred history. But what does that retelling entail? Through study of four of its main episodes, from their long inter-female dialogues to the protagonists' encounters with jinn , dervishes, and foreigners, this book explores the taʿziyeh repertoire's compositional features. Combining a wide range of historical scripts, largely unpublished manuscripts, with witness accounts, it tracks the tradition's development from Safavid to Qajar Iran asking, who were its contributors? And, how have they left their mark?